O PAPEL DE DUAS SESSÕES EXTENUANTES COM DIFERENTES INTERVALOS ENTRE AS SESSÕES - 24 e 48 HORAS - E O EFEITO PROTETOR DA CARGA - Rodrigo Bergome Muniz; Igor de Sá Maia; Rômulo Oswaldo Camacho; Pierre Augusto-Silva; Victor Magalhães Curty (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
It is reported that a single session of resistance exercise provides to our bodies with an adaptation of shape subsequent exercises do not have the same effect stressful. Objective: To evaluate the repeated bout effect in exercise sessions with different intervals after a week of the first session. Materials and Methods: 14 men (18 to 30 years) engaged in strength training for a minimum of 6 months were divided into two groups A and B. The participants performed five sets, maximum repetitions with two minutes of rest between sets at 85% 1RM in biceps curl exercise unilateral Scott on the bench with the non-dominant arm. The second training session was performed 24 h later, for group A, and 48 hours later for group B. Blood samples were collected in pre measures, 24h, 48h, 72h and 96h, arm girth measurements, range of motion in flexion and extension, and measures of subjective perception of pain on palpation and by extension, before and after exercise every day of the tests. Results: When the first two exercise sessions were performed with shorter rest intervals (24 hours) due to increased pain sensation, maintaining range of motion and reduced activity for longer serum CK higher. Conclusion: Exercises with short intervals (24 hours) may modulate the repeated bout effect increasing the values of physiological variables and significant reductions in joint range of motion.